Bedford Building at 105 Bedford Street, ca. 1955 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of the Bedford Building, located at 105 Bedford Street at the corner of Bedford and Summer Streets. Signage and a large clock adorn the facade as well as the northeast and southeast elevations of the building. A street light is located on the sidewalk in front of the entrance to the building. Designed by Cummings and Sears, 1875-76 9 3/8 x 7 1/2, 9 3/4 x 8 overall Photographs